External Tests of Peer Review Validity Via Impact Measures - Gallo, Stephen A.; Glisson, Scott R. (Frontiers in Research Metrics and Analytics, 2018)
Peer review is used commonly across science as a tool to evaluate the merit and potential impact of research projects and make funding recommendations. However, potential impact is likely to be difficult to assess ex-ante; some attempts have been made to assess the predictive accuracy of these review decisions using impact measures of the results of the completed projects. Although many outputs, and thus potential measures of impact, exist for research projects, the overwhelming majority of evaluation of research output is focused on bibliometrics. We review the multiple types of potential impact measures with an interest in their application to validate review decisions. A review of the current literature on validating peer review decisions with research output impact measures is presented here; only 48 studies were identified, about half of which were US based and sample size per study varied greatly. 69% of the studies employed bibliometrics as a research output. While 52% of the studies employed alternative measures (like patents and technology licensing, post-project peer review, international collaboration, future funding success, securing tenure track positions, and career satisfaction), only 25% of all projects used more than one measure of research output. Overall, 91% of studies with unfunded controls and 71% of studies without such controls provided evidence for at least some level of predictive validity of review decisions. However, several studies reported observing sizable type I and II errors as well. Moreover, many of the observed effects were small and several studies suggest a coarse power to discriminate poor proposals from better ones, but not amongst the top tier proposals or applicants (although discriminatory ability depended on the impact metric). This is of particular concern in an era of low funding success, where many top tier proposals are unfunded. More research is needed, particularly in integrating multiple types of impact indicators in these validity tests, as well as considering the context of the research outputs relative to goals of the research program and concerns for reproducibility, translatability and publication bias. In parallel, more research is needed focusing on the internal validity of review decision making procedures and reviewer bias.